Hire-purchase agreement in Malaysia: what the hirer needs to know? / Nur Irinah Mohamad Sirat, Nurul Mazrah Manshor and Dr. Rohayati Hussin - Mohd Sirat, Nur Irinah; Manshor, Nurul Mazrah; Hussin, Rohayati (Universiti Teknologi MARA, Kedah, 2024)
Are you thinking about purchasing a car in Malaysia? Let us talk about hire purchase financing and how it can help you make your dream car a reality! The Hire Purchase Act 1967 (HPA) is a consumer credit option widely used for buying vehicles. This law was enacted to protect your rights as a consumer and ensure everyone involved in the purchase is treated fairly. A The HPA outlines the formation and nature of the hire purchase agreement, rights and obligations of parties in the hire purchase agreements, essential terms in the hire purchase agreement and processes and procedures for repossession. Therefore, it is essential to understand these terms to make the best decisions for your financial future. Do not let legal complications hinder your car-buying journey - let us explore hire purchase financing together!